Emerging pharmacotherapies for the treatment of atrial fibrillation. (2nd January 2018) - Capucci, Alessandro; Cipolletta, Laura; Guerra, Federico; Giannini, Irene
ABSTRACT: Introduction : The main aim of current research on the field of atrial fibrillation (AF) treatment is to find new antiarrhythmic drugs with less side effects. Areas covered : Dronedarone and vernakalant showed promising result in term of efficacy and safety in selected patients. Ranolazine and colchicine are obtaining a role as a potential antiarrhythmic drug. Ivabradine is used in experimental studies for the rate control of AF. Moreover, new compounds (vanoxerine, moxonidine, budiodarone) are still under investigation. Monoclonal antibodies or selective antagonist of potassium channel are under investigation for long term maintenance of sinus rhythm. Clinical evidence and new pharmacological investigation on new drugs will be accurately reviewed in this article. Expert opinion : Dronedarone use is not recommended in patients with symptomatic heart failure (HF), NYHA class III-IV, depressed ventricular function and permanent AF, especially in patients assuming a concomitant therapy with digoxin. Vernakalant had superior efficacy than amiodarone, flecainide and propafenone in single studies and similar efficacy to direct current cardioversion. Several of the developing drugs examined in this paper show an interesting potential, in particular the research on selective ionic channel inhibition and on compounds which reduce the inflammation state, especially after ablation or surgery.